2022
DOI: 10.3390/cancers14246103
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of the Multifaceted Role of SOX11 in Cancer

Abstract: SRY-box transcription factor 11 (SOX11), as a member of the SOX family, is a transcription factor involved in the regulation of specific biological processes and has recently been found to be a prognostic marker for certain cancers. However, the roles of SOX11 in cancer remain controversial. Our study aimed to explore the various aspects of SOX11 in pan-cancer. The expression of SOX11 was investigated by the Genotype Tissue-Expression (GTEX) dataset and the Cancer Genome Atlas (TCGA) database. The protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“… 31 Multiple studies demonstrated that the aberrant expression of Sox11 is related to cancer progression and prognosis. 16 , 32 , 33 To investigate the role of Sox11 in OLP‐associated OSCC progression, we first evaluated the expression of Sox11 in normal oral mucosa ( n = 20), OLP ( n = 40), and OSCC tissues ( n = 120). Fortunately, we found that Sox11 expression was significantly elevated in OLP tissues relative to normal oral mucosa tissue samples, with further Sox11 upregulation in OSCC tissues relative to OLP tissues (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 Multiple studies demonstrated that the aberrant expression of Sox11 is related to cancer progression and prognosis. 16 , 32 , 33 To investigate the role of Sox11 in OLP‐associated OSCC progression, we first evaluated the expression of Sox11 in normal oral mucosa ( n = 20), OLP ( n = 40), and OSCC tissues ( n = 120). Fortunately, we found that Sox11 expression was significantly elevated in OLP tissues relative to normal oral mucosa tissue samples, with further Sox11 upregulation in OSCC tissues relative to OLP tissues (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Sox11, a member of the SOX family, plays a regulatory role in specific biological processes 31 . Multiple studies demonstrated that the aberrant expression of Sox11 is related to cancer progression and prognosis 16,32,33 . To investigate the role of Sox11 in OLP‐associated OSCC progression, we first evaluated the expression of Sox11 in normal oral mucosa ( n = 20), OLP ( n = 40), and OSCC tissues ( n = 120).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the promote an immune microenvironment, especially the infiltration of CD4+ T cells and macrophage immune cells 12 . For example, SOX11, a member of the same family as SOX2, is a novel tumor therapeutic target because of its immune infiltration potential 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Sox4 overexpression is associated with lymph node metastasis in Tongue squamous cell carcinoma (TSCC) [14]. While the impact of Sox11 protein expression in cancer progression is controversial, recent research links dysfunctional expression with increased cancer cell survival, inhibited cell differentiation, and tumor progression [15,16], in contrast, a correlation between Sox-18 and CRC prognosis is reported [17].…”
Section: Introductionmentioning
confidence: 99%